2004
DOI: 10.1080/09638280400000203
|View full text |Cite
|
Sign up to set email alerts
|

Whiplash injuries in Finland--the possibility of some sociodemographic and psychosocial factors to predict the outcome after one year

Abstract: Several sociodemographic and psychosocial factors can have relation to the deterioration of health experienced after whiplash injury but in this prospective study they proved to have only limited prognostic value in the long term symptoms with the exception of the education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…The increase in neck pain seen with lower education levels is supported by previous studies of whiplash patients [9,[24][25][26], but the mechanism for this association is not clear. It is likely that patients with lower education levels are more likely to have manual jobs, and therefore it is possible that this group of patients had more neck pain prior to the injury due to their occupation.…”
Section: Discussionsupporting
confidence: 66%
“…The increase in neck pain seen with lower education levels is supported by previous studies of whiplash patients [9,[24][25][26], but the mechanism for this association is not clear. It is likely that patients with lower education levels are more likely to have manual jobs, and therefore it is possible that this group of patients had more neck pain prior to the injury due to their occupation.…”
Section: Discussionsupporting
confidence: 66%
“…In a recent prospective study, Sterling et al (2005) maintain that both physical factors and psychological distress play a role in the recovery or non-recovery from whiplash injury. According to several studies (e.g., Wallis et al 1996Wallis et al , 1997Richter et al 2004;Miettinen et al 2004;Nederhand et al 2004;Ferrari et al 2005;Hendriks et al 2005;Guez et al 2005), socio-demographic, cultural and psychological factors add to physical factors in aVecting the shortand long-term outcome after whiplash injury, and are listed among the predictive factors for the subjects to develop chronic neck pain disability (see Pain).…”
Section: Involvement Of the Sympathetic Nervous System In Wadmentioning
confidence: 99%
“…Most recently, Carroll et al performed a meta-analysis of the literature pertaining to whiplash injury. When considering all whiplash patients, 44% to 66% of patients had symptoms at one year, but only 12% reported daily neck pain and only 9% reported significant health impairment as a result of the whiplash injury [26][27][28]. Others have shown that 90% of patients presenting with neck pain and neurological signs (WAD III) have continued symptoms at one-year following the injury [29].…”
Section: Discussionmentioning
confidence: 99%